Relationship between Vocabulary Mastery and Interview Report Writing Skills of Elementary School Students - Purwati, Tina; Wirawan, Gunta; Suprapto, Wasis (Institut Agama Islam Negeri Palopo, 2023)
This research aims to: 1) describe the vocabulary mastery of class IV students at SDS IT Nurul Islam Singkawang; 2) describe the skills in writing reports from interviews of class IV students at SDS IT Nurul Islam Singkawang; 3) find out how big the relationship is between vocabulary mastery and the skill of writing reports from interviewers of class IV students at SDS IT Nurul Islam Singkawang. The research used is correlational research with quantitative methods. The population in this study were fourth grade students at SDS IT Nurul Islam Singkawang. The research sample was taken purposively (purposefully) and was selected using 2 steps. (1) based on the result of interviews with teachers (2) based on suggestions from teachers. The prerequisite test carried out is a normality test using the Chi-square formula and a linearity test is carried out see whether the data is linear or not. Data were analyzed univariately with a significance level of 5% (0,05) for testing the first hypothesis using the Pearson Product Moment correlation technique. The results og the research show that: 1) From the results of calculating the overall average score for students’ vocabulary mastery of 71%, it can be concluded that the vocabulary mastery of class IV students at SDS IT Nurul Islam Singkawang is quite good. 2) From the results of calculating the skill scores for writing reports from student interviews, the average score obtained was 75%. It can be concluded that the skills for writing reports from interviews for class IV students at SDS IT Nurul Islam Singkawang are quite good. 3) There is a significant relationship between vocabulary mastery and student interview report writing skills with a correlation value of 0,504 and a coefficient of determination of 25,40%.